INFORMED CONSENT SIRKUMSISI DI PUSKESMAS WARU, KABUPATEN PAMEKASAN, PROVINSI JAWA TIMUR, PERIODE 1 JANUARI – 31 DESEMBER 2013 - Hamim Tohari; Santosa Santosa; Akhmad Ismail (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2016)
Background : Health service has 2 inseparable parties, those are doctor and patient. Relationship between them is regulated by law giving rise to doctor and patient's rights and obligations. One of the doctor's obligation in medical service is giving informed consent for all action that will be done to the patient. All medical action are preceeded by informed consent, including circumcision.Aim : To determine the implementation of informed consent for circumcision done in Puskesmas Waru, Pamekasan Regency, East Java Province.Method : This research is a descriptive study. This research uses survaillance method done by collecting data, with informed consent as the sample which was gathered from medical record of circumcision in Puskesmas Waru, Pamekasan Regency, East Java Province done in January 1st - December 31st 2013. Collected data are displayed in the form of diagrams and tables.Result : This research shows that, based on diagnosis and medical action procedure, 100% of samples have complete criteria, 100% explains Purpose of Medical Action, 100% explains Risks and Complications, 0% explains Costs Estimation, 100% of agreement to circumcision are written, and 100% of the agreement signed by both informant and approver.Conclusion : Circumcision in Puskesmas Waru have been explained quite completely but some information was not explained. Agreement of circumcision in Puskesmas Waru have been written as explained in current Minister of Health Regulation and Statute.